Life’s homochirality: Across a prebiotic network - S. Furkan Ozturk; Dimitar D. Sasselov (Proceedings of the National Academy of Sciences, 2025)
For centuries, scientists have been puzzled by the mystery of life’s biomolecular homochirality—the single-handedness of biological compounds. Sugars and nucleic acids are right-handed, while amino acids are left-handed in biological systems. Likewise, certain metabolites are homochiral, though their handedness varies. However, efforts to address the homochirality problem have often focused on a single compound, a single molecular class, or invoke an extraterrestrial origin. Here, we emphasize the importance of achieving homochirality across an entire prebiotic chemical network and explore a terrestrial pathway for its emergence. This pathway is supported by recent experimental results from several independent studies, as well as analyses of pristine asteroid materials. Our analysis identifies the genome as a key site for achieving network-scale homochirality on early Earth and addresses the opposite handedness of D -nucleic acids and L -peptides in biology through nonenzymatic, stereoselective coded peptide synthesis.